2006
DOI: 10.1016/j.virol.2006.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Human CD8+ cytotoxic T cell responses to adenovirus capsid proteins

Abstract: Adenoviruses (Ads) cause fatal disease in allogeneic stem cell transplant recipients, but there is no established therapy. Ad-specific CD8+ T cells were detected in PBMC from healthy adults at a mean frequency of 77 per 10(5) CD8+ T cells (range 8-260) by interferon-gamma ELISPOT and cytokine flow cytometry assays. CD8+ T cell lines from 7 of 7 donors exhibited MHC-class-I-restricted killing of targets expressing the capsid protein hexon. In contrast, cytotoxicity against the capsid proteins fiber and penton b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 36 publications
3
71
0
Order By: Relevance
“…The well-characterized DPB1*0401-restricted epitope TLLYVLFEV (H913-921) is contained within this region, along with minimally four additional peptides recognized by Ad-specific T cells ( Supplementary Fig. S2) (Tang et al, 2006). We confirmed that SP98/SP99, each containing the TLLYVLFEV sequence, were recognized in the context of both DPB1*0401 and DPB1*0402 and further identified epitopes restricted by DQB*0402 and Cw*0702 within H906-928.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…The well-characterized DPB1*0401-restricted epitope TLLYVLFEV (H913-921) is contained within this region, along with minimally four additional peptides recognized by Ad-specific T cells ( Supplementary Fig. S2) (Tang et al, 2006). We confirmed that SP98/SP99, each containing the TLLYVLFEV sequence, were recognized in the context of both DPB1*0401 and DPB1*0402 and further identified epitopes restricted by DQB*0402 and Cw*0702 within H906-928.…”
Section: Discussionsupporting
confidence: 69%
“…We confirmed that SP98/SP99, each containing the TLLYVLFEV sequence, were recognized in the context of both DPB1*0401 and DPB1*0402 and further identified epitopes restricted by DQB*0402 and Cw*0702 within H906-928. Indeed, multiple investigators have reported hexon-specific responses within this region after natural infection (Tang et al, 2004(Tang et al, , 2006, after priming with intact Ad (Olive et al, 2002) or a modified Ad vector , and using 30-mer hexon peptides . Predominantly CD4 + T cells respond to Ad in healthy adults and paediatric patients post-HPCT, which contrasts with the largely CD8 + T-cell response to most viral pathogens (Appay et al, 2008;Yewdell & Bennink, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations